Tipos de exploração pecuária e infecção por Leptospira interrogans em Minas Gerais, 1998-2002 - Isabela Farnezi Veloso (2004)
17.993 bovine sera from Minas Gerais state were analized through microscopic agglutination test to check the prevalence of antiLeptospira interogans agglutinins in three groups of animals from 1998-2002. To recognize the forms of animal production in different municipalities it was used the indicators wich reflect the demographic systems between steer/cow ratio and caracterized the risks areas of infecction by L. interrogans. The most frequently observed serovars were hadjo (Norma) (22.66%), hardjo (OMS) (18.26%), hardjo (hardjoboivis) (13,79%) and wolffi (9,73%). Analysing the frequency of anti Leptospira interrogans agglutinins according to the types of exploration it is ended the relation between those frequencies and forms of production starter reasing (calves), re-criate, complete cycle and fattening (termination). The most of higher risk counties of infection by hardjo (OMS), hardjo (Norma), wolffi and pomona are dedicated of re-criate and fattening (termination). The most of lesser risk counties of infectionof the same sorotypes are in the starter reasing (calves).